Microbiota and cancer: host cellular mechanisms activated by gut microbial metabolites - Sofia A. Tsvetikova; Elena I. Koshel (Elsevier, 2020)
In recent years, more and more data indicate the effect of human microbiota on carcinogenesis. Despite the numerous studies on the relationship between gut microbiota and carcinogenesis, the exact mechanisms of this interaction are not well studied. It becomes apparent that this relationship can be mediated by microbial metabolites. Mechanisms of some well-known bacterial genotoxins and oncogenes, such as colibactin, CagA, IpgD, VirA, P37, have been studied in detail. At the same time, a role in carcinogenesis of a large group of gut microbial metabolites, including short-chain fatty acids, polyamines, and products of polyphenol and tryptophan catabolism, is less well understood. However, more and more evidence data show the effect of bacterial metabolites on cancer development and progression. In this review, we summarize relevant data regarding the possible mechanisms that can account for the effects of gut microbial metabolites mentioned above in carcinogenesis.